ARSITEKTUR KEUANGAN, KOMPENSASI DIREKSI DAN NILAI PERUSAHAAN DI INDONESIA - Widnyana, I Wayan; Widyawati, Sapta Rini (JUIMA : JURNAL ILMU MANAJEMEN, 2018)
This study aims to analyze and explain the influence of financial architecture dimension consisting of ownership structure, capital structure and corporate governance as well as adding another variable that is directors compensation to firm value. This study was conducted at companies listed in Indonesia Stock Exchange (IDX) period 2016 using secondary data source, consisting of 543 companies, of which 437 companies as a sample because it has complete data. The analysis method used is linear regression analysis, determination analysis and t test. The results showed that the financial architecture, capital structure, corporate governance and directors compensation have a positive and significant impact on firm value.